2018
DOI: 10.4236/wja.2018.81003
|View full text |Cite
|
Sign up to set email alerts
|

Emerging HIV Epidemic in the North-Eastern State of Assam, India: An Exploratory Study Using Mixed-Methods Approach

Abstract: Background: The national HIV scenario in India has improved impressively during past two decades. Contrastingly, the State-level HIV sentinel surveillance and routine programme data from various testing facilities indicated an increasing HIV prevalence among antenatal clinic attendees and female sex workers (FSWs) in three districts of Assam. Objectives: 1) To explore the reasons behind increasing adult HIV prevalence and 2) To understand the role of FSW and Migrants/long distance truckers as drivers of the HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…1 A study by Bhattacharjya et al also showed that the two southern districts-Cachar et al have the highest percentage of cases around 25% in comparison with other districts. 2 In India, the prevalence of HIV infection in pregnant women ranges from 0.7% to 1.2%. 3 Cervical intraepithelial neoplasia occurs as a continuum of atypical metaplasia caused as a result of persistent HPV infection due to immune suppression.…”
Section: Introductionmentioning
confidence: 99%
“…1 A study by Bhattacharjya et al also showed that the two southern districts-Cachar et al have the highest percentage of cases around 25% in comparison with other districts. 2 In India, the prevalence of HIV infection in pregnant women ranges from 0.7% to 1.2%. 3 Cervical intraepithelial neoplasia occurs as a continuum of atypical metaplasia caused as a result of persistent HPV infection due to immune suppression.…”
Section: Introductionmentioning
confidence: 99%